2000
DOI: 10.1002/cjce.5450780620
|View full text |Cite
|
Sign up to set email alerts
|

Method to determine molecular diffusivities of phenol in bitumen

Abstract: Phenols, carboxylic acids and other water‐soluble compounds in bitumen constitute a potential source of groundwater pollution. To assess the extent of damages that could result from a spill, a water extraction method was used to determine the molecular diffusion of phenol in bitumen. This method involves the diffusion of phenol through bitumen into the flowing water in a well‐stirred cell. From the phenol concentration in water, the phenol flux and hence the phenol diffusion coefficient in bitumen can be deduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…where C s,n is the concentration of the volatile solvent in nitrogen gas, Q is the volumetric flow rate of nitrogen gas at [1] Modified transpiration [3,4] Taylor dispersion [5] Nuclear magnetic resonance [6][7][8][9][10] …”
Section: Modified Transpiration Techniquementioning
confidence: 99%
“…where C s,n is the concentration of the volatile solvent in nitrogen gas, Q is the volumetric flow rate of nitrogen gas at [1] Modified transpiration [3,4] Taylor dispersion [5] Nuclear magnetic resonance [6][7][8][9][10] …”
Section: Modified Transpiration Techniquementioning
confidence: 99%
“…The reduced velocity v/(1+b) can be regarded as the effective phenol propagation rate. The boundary condition, which defines the flux into the water phase at the bitumen-aquifer interface, becomes: Comparing Equations (14), (15) with Equations (1), (2), it is evident that the solution to Equations (14) and (15) can be obtained simply by replacing the phenol concentration C(x,y,t), velocity v, dispersion coefficients D w,x and D w,y in Equation (4) with the corresponding reduced entities, i.e., the entities divided by the factor of (1+b).…”
Section: Mass Balance Of Phenol In Aquifermentioning
confidence: 99%
“…Based on the "decouple" assumption, the phenol convective-dispersive equation in water phase can be set up 4 (Equation 1) with a flux boundary condition (Equation 2): (2) where A = transfer area = Ldz, <L 2 >, J = phenol flux into the water phase, J (mg/s), C o = effective phenol concentration in water/bitumen emulsion, gm of phenol/cc of emulsion, v = interstitial velocity in porous medium cm/s. It has been known that Green's function does satisfy the convective-dispersive equation 8 , therefore it is a general solution to Equation (1).…”
Section: Continuous Finite Line Source With Time-dependent Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds, which are soluble both in oil and water, can leach slowly into the subsurface aquifer, posing a threat of groundwater contamination to the environment. Previous studies (Tang, 1999;Tang and Zhang, 2000) revealed that molecular diffusion of phenol in bitumen was the rate-determining step and the transfer mechanism could be adequately described by a de-coupled second-order convective-dispersive equation from which the diffusion coefficients of phenol were determined to be 2:2 10 8 cm 2 /s at 4 ı C in water-bitumen emulsion and 4:0˙0:3 10 8 cm 2 /s at 22 ı C in bitumen.…”
Section: Introductionmentioning
confidence: 99%